EFEKTIVITAS MODUL LESSON STUDY DALAM PEMBELAJARAN GEOGRAFI BAGI MAHASISWA KPL - Nur Wakhid Hidayat; Sumarmi Sumarmi; Ach. Amirudin (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2017)
KPL is one of the programs that must be implemented by students of the department of education at Universitas Negeri Malang (UM). The MPA Student is required to implement the program that is determined to implement the lesson study in the framework of lesson study. Based on the facts in the field, there are many obstacles faced by MPA Students, among them (1) the lack of presence of field supervisor in the learning activities; (2) lack of guidance of teachers in learning activities; (3) lack of material handout lesson study. Based on the problem, the researcher wanted to focus the research on how the effectiveness level of Lesson Study Module in Geography Learning for Students at school MPA activity. This research is one of descriptive research by using qualitative approach. The subjects of this study are students who have taken the MPA. Based on the research results can be seen that 77% of students give positive responses to the module. The developed modules are very effective and worthy of use for MPA Students. The developed modules can be used as reference material for MPA Students in conducting lesson study activities. In the future, it is expected that there will be further research in the field of lesson study geography. It is also recommended that modules can be experimented so that modules can be developed again for the better.KPL adalah salah satu program yang wajib dilaksanakan oleh mahasiswa jurusan kependidikan di Universitas Negeri Malang. Mahasiswa KPL wajib melaksanakan program yang sudah ditentukan, yaitu melaksanakan pembelajaran dalam kerangka lesson study. Berdasarkan fakta di lapangan banyak sekali kendala yang dihadapi Mahasiswa KPL, di antaranya (1) kurangnya kehadiran dosen pembimbing lapangan dalam kegiatan pembelajaran; (2) kurangnya bimbingan guru pamong dalam kegiatan pembelajaran; (3) minimnya materi handout lesson study. Berdasarkan permasalahan tersebut peneliti ingin memfokuskan penelitian pada bagaimana tingkat efektifitas Modul Lesson Study dalam Pembelajaran Geografi bagi Mahasiswa pada kegiatan KPL sekolah. Penelitian ini adalah salah satu penelitian deskriptif dengan menggunakan pendekatan kualitatif. Subjek penelitian ini adalah Mahasiswa yang pernah menempuh KPL. Berdasarkan hasil penelitian dapat diketahui bahwa 77% mahasiswa memberikan respon positif terhadap modul. Modul yang dikembangkan sangat efektif dan layak digunakan bagi Mahasiswa KPL. Modul yang dikembangkan dapat dijadikan bahan rujukan bagi Mahasiswa KPL dalam melaksanakan kegiatan lesson study. Kedepan diharapkan ada penelitian lanjut di bidang lesson study geografi. Disarankan juga agar modul bisa dieksperimenkan sehingga modul dapat dikembangkan lagi menjadi lebih baik lagi.